"Das Leben ist kurz, die Kunst ist lang": (Un-) Endlichkeit aus medizinhistorischer Perspektive - Leven, Karl-Heinz; Freiburg, Rudolf; Lubkoll, Christine; Schoberth, Wolfgang; Weth, Thomas; Wilms, Jörn (Unendlichkeit: Erlanger Universitätstage Ansbach 2015, 2016)
Keywords: Unendlichkeit; Literatur; Alexander Pope; Edward Young; Thodizee; Gott; Ewigkeit; Zeit; Raum

Effects of the COVID-19 Restrictions on Eating Behaviour and Eating Disorder Symptomology in Female Adolescents - Muth, Lois; Leven, Karl-Heinz; Moll, Gunther; Kratz, Oliver; Horndasch, Stefanie (International Journal of Environmental Research and Public Health, 2022)
Confinement due to the COVID-19 pandemic imposes a burden on adolescents worldwide and may seriously impact patients with an eating disorder (ED). The current FRanconian Anorexia Nervosa during COVID-19 (FRANCO) study explored (1) perceived change of depressive and ED symptomology during lockdown, (2) the role of social media, and (3) coping strategies of anorexia nervosa (AN) patients and clinical as well as healthy comparison groups. From June 2021 to September 2021, 222 female adolescents (19 with AN, 20 with depression, 45 with a self-reported psychiatric disorder (SRPD), and 138 controls) aged 11.2 to 18.9 years completed a one-time anonymous survey retrospectively reporting back on ED and depressive symptomology before and during the pandemic, the impact of social media, and coping strategies. A reduced quality of life (QoL) due to confinement was observed in almost half of female adolescents. All groups reported a significant perceived increase of disordered eating, overeating, anxiety, and depressive symptoms and emotion-regulation problems. In AN patients, significantly higher percentual deterioration of disordered eating and anxiety and depressive symptoms was found. For controls, a younger age and higher susceptibility of the sociocultural body image significantly correlated with increased disordered eating. Large-scale media literacy interventions are recommended.
CRIS-Team Scopus Importer:2022-08-12
Keywords: adolescents; anorexia nervosa; COVID-19 pandemic; depression

Kyle Harper, Plagues Upon the Earth. Disease and the Course of Human History. Princeton, NJ, Princeton University Press 2021 - Leven, Karl-Heinz (2023)
CRIS-Team Scopus Importer:2023-12-22